Comparative Legal Analysis of the Integration Mechanisms of the European Union and the Eurasian Economic Community - S. N. Yaryshev; E. T. Baildinov (Московский журнал международного права)
The article is dedicated to the comparative analysis of the mechanism of implementation of EU goals (values) in the framework of «Lisbon» integration legal order, on one hand, and of the legal ability of the Eurasian Economic Community on the other.